2021
DOI: 10.5005/jp-journals-10071-23791
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy before 14 Days: Is It Associated with Better Outcomes in Pediatric Patients on Prolonged Mechanical Ventilation?

Abstract: A bstract Introduction With the advancement of pediatric critical care services across India, many children require prolonged mechanical ventilation (MV), and tracheostomy is recommended to them. However, many pediatric intensivists have concerns regarding the safety, feasibility, and outcome of tracheostomy. We aimed to analyze clinical characteristics, indication, duration, and outcome of tracheostomized children with respect to timing of tracheostomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
4
2
1
Order By: Relevance
“…Rane et al reported lower neonatal mortality in ET group but it was not found to be an independent risk factor 22 . A recent pediatric study reported statistically significant higher number of decannulation in ET group 13 . We did not find any difference in decannulation rate between ET and LT patients except in NMD category.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Rane et al reported lower neonatal mortality in ET group but it was not found to be an independent risk factor 22 . A recent pediatric study reported statistically significant higher number of decannulation in ET group 13 . We did not find any difference in decannulation rate between ET and LT patients except in NMD category.…”
Section: Discussioncontrasting
confidence: 64%
“…22 A recent pediatric study reported statistically significant higher number of decannulation in ET group. 13 We did not find any difference in decannulation rate between ET and LT patients except in NMD category. The reason for significantly delayed decannulation in NMD cases was due to inclusion of many cases of acute cervical cord injury and myelitis in ET group.…”
Section: Neuromuscular Diseasescontrasting
confidence: 50%
See 2 more Smart Citations
“…La indicación de traqueostomía por VMI prolongada en población pediátrica es más infrecuente y se encuentra menos estandarizada, y aunque tiene los mismos potenciales efectos beneficiosos que en adultos, la evidencia tiene su origen solo en estudios de cohorte retrospectivos (11)(12)(13). La tendencia observada en pacientes pediátricos es al aumento en la consideración de traqueostomía para los niños con VMI prolongada.…”
Section: Introductionunclassified